Trends Of Online Vegetable Shopping Decisions In Bale Hydroponics In The Covid-19 Pandemic Era - Budi Handoko Budi Handoko; Damara Dinda Nirmalasari Zebua (Inovbiz: Jurnal Inovasi Bisnis, 2021)
This study aims to 1) Knowing the current trend of online vegetable shopping 2) Knowing consumer decision making in online shopping. The location selection was carried out purposively by considering that Bale Hydroponics is an organic vegetable marketing business that markets organic vegetables online. This study uses a qualitative method. The observed variables are factors that influence consumer decisions in making online purchases, namely lifestyle, product quality, price and ease of payment/transaction. The results showed that six factors that influence consumer decisions in online shopping at Bale Hidroponik are lifestyle, quality availability information, relatively affordable prices, ease of payment/transaction, easy access, attractive promotions, quality service and delivery time.